The Effect of Antimalarial Campaigns on Child Mortality and Fertility in Sub-Saharan Africa - Joshua Wilde; Bénédicte Apouey; Joseph Coleman; Gabriel Picone (Institute of Labor Economics (IZA), 2020)
We examine the extent to which recent declines in child mortality and fertility in Sub- Saharan Africa can be attributed to insecticide-treated bed nets (ITNs). Exploiting the rapid increase in ITNs since the mid-2000s, we employ a difference-in-differences estimation strategy to identify the causal effect of ITNs on mortality and fertility. We show that the ITN distribution campaigns reduced all-cause child mortality, but surprisingly increased total fertility rates in the short run in spite of reduced desire for children and increased contraceptive use. We explain this paradox in two ways. First, we show evidence for an unexpected increase in fecundity and sexual activity due to the better health environment after the ITN distribution. Second, we show evidence that the effect on fertility is positive only temporarily – lasting only 1-3 years after the beginning of the ITN distribution programs – and then becomes negative. Taken together, these results suggest the ITN distribution campaigns may have caused fertility to increase unexpectedly and temporarily, or that these increases may just be a tempo effect – changes in fertility timing which do not lead to increased completed fertility.
Keywords: I15; J13; O10; O15; 330; Malaria; bed nets; child mortality; fertility; Sub-Saharan Africa